The attitude-behaviour gap in biosecurity: Applying social theories to understand the relationships between commercial chicken farmers' attitudes and behaviours - Pao, Hai-Ni; Jackson, Elizabeth; Yang, Tsang-su; Tsai, Jyan-syu; Hwang, Yi-ti; Sung, Watson HT; Pfeiffer, Dirk U (Frontiers Media S.A., 2023)
Introduction: Traditionally, it is believed that people's behaviours align with their attitudes; however, during COVID-19 pandemic, an attitude-behaviour gap in relation to preventive measures has been observed in recent studies. As such, the mixed-methods research was used to examine the relationships between farmers' biosecurity attitudes and behaviours in Taiwan's chicken industry based on the cognitive consistency theory.